Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1152/japplphysiol.00801.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of middle cerebral artery blood velocity during recovery from dynamic exercise in humans

Abstract: We sought to examine the regulation of cerebral blood flow during 10 min of recovery from mild, moderate, and heavy cycling exercise by measuring middle cerebral artery blood velocity (MCA V). Transfer function analyses between changes in arterial blood pressure and MCA V were used to assess the frequency components of dynamic cerebral autoregulation (CA). After mild and moderate exercise, the decreases in mean arterial pressure (MAP) and mean MCA V (MCA Vm) were small. However, following heavy exercise, MAP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 29 publications
1
31
1
Order By: Relevance
“…MBV and VCI in the MCA did not differ between pre-treatment and the pre-task baseline in both trials, suggesting that neither vasoconstriction nor vasodilation occurred in the cerebral region after the end of exercise, partly consistent with the previous study which reported no significant change in MCA during 1 to 8 min after the exercise at HR of 90, 120, and 150 bpm [21]. …”
Section: Discussionsupporting
confidence: 89%
“…MBV and VCI in the MCA did not differ between pre-treatment and the pre-task baseline in both trials, suggesting that neither vasoconstriction nor vasodilation occurred in the cerebral region after the end of exercise, partly consistent with the previous study which reported no significant change in MCA during 1 to 8 min after the exercise at HR of 90, 120, and 150 bpm [21]. …”
Section: Discussionsupporting
confidence: 89%
“…In both supine and upright positions, 5 min steady‐state baseline ABP and MCA V beat‐to‐beat signals were re‐sampled at 2 Hz for spectral analysis (Ogoh et al., 2005a, b, ). Dynamic CA was calculated as the transfer function gain and phase shift between fluctuations in ABP and MCA V (Ogoh et al., 2005a, b, ). The transfer gain and phase shift reflect the relative amplitude and time relationship between the changes in ABP and MCA V over a specified frequency range.…”
Section: Methodsmentioning
confidence: 99%
“…While cerebral autoregulation is well-maintained following moderate intensity exercise (Ogoh et al , 2007; Murrell et al , 2007; Willie et al , 2013), two studies suggest that more intense exercise may produce a lasting cerebral autoregulatory deficit. Specifically, Ogoh et al (2005) found reduced dynamic cerebral autoregulation (as assessed by transfer function) during heavy cycle exercise and Bailey et al (2011) found reduced dynamic cerebral autoregulation (as assessed by thigh-cuff release) during recovery from a recumbent cycle peak test.…”
Section: Part 2: Exploration Of Different Exercise Models That Generamentioning
confidence: 99%